Peran Learning Goal Orientation dan Big Five Personality terhadap Adaptabilitas Karier Siswa SMK - Jati Fatmawiyati; Duta Nurdibyanandaru; Dewi Retno Suminar (Psympathic: Jurnal Ilmiah Psikologi)
The purpose of this study is to investigate learning goal orientation (LGO) and Big Five Personality in effect with carrier adaptability. This study used quantitative approach. Simple random sampling technique was used to recruit 93 twelve-grades SMKN "X" Malang students majoring in Teknik Komputer dan Jaringan (TKJ) and Rekayasa Perangkat Lunak (RPL). We used adapted instruments consist of LGO Scale, Big Five Inventory (BFI) and Career Adapt-Abilities Scale (CAAS). The simultaneously regression test shows that both LGO and Big Five Personality has an effect to carrier adaptability (37%). LGO partially has effect on carrier adaptability. For all big five personality dimensions, opennes to experience has effect to carrier adaptability but other dimensions such as extraversion, conscientiousness, neuroticism, and agreeableness has no effect.